ANALISA DAN PERANCANGAN SISTEM KOMPUTERISASI PERHITUNGAN HPP PADA PT ALCORINDO SEJAHTERA DIVISI PENGECORAN LOGAM - Theresia Retnoq R; . Nurasiah (Universitas Insan Pembangunan Indonesia, 2016)
1.Theresia Retno R.( theresiaretno88@gmail.com)2.Nurasiah, S. Kom., MMSI. (nurash_ip@yahoo.com)Mahasiswa Jurusan Komputerisasi Akuntansi, STMIK Insan PembangunanDosen, STMIK Insan PembangunanJl. Raya Serang Km. 10 – Bitung – Tangerang – 15810Telp : 021.59492836/ 021.59492837E-mail : info@ipem.ac.idABSTRACTResearch by the author in Alcorindo PT Sejahtera in foundry division is meant to be able toknow the COGS calculation system that runs in Alcorindo PT Sejahtera. After doingresearch, the authors designed a computerized system to improve the system that runs toachieve maximum results. The authors collected data using interview techniques, observationand literature. Whereas in designing computerized COGS calculations system, the authoruses a UML modeling tool that aids the development of object-oriented systems.Keywords: HPP, metal casting, systems, UML